Epistemologiczny kontekst pedagogiki i jej tożsamość = Epistemological context of education and its identity - Magda-Adamowicz, Marzenna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Against a background of epistemological theory of the truth in educational sciences, the author has expressed her concern about: 1/ the object of scientific interest of educators, 2/ low self-esteem of education theorists, 3/ the fact that the object of academic interests of educators often interferes with the areas studied by other sciences, e.g., psychology, sociology, philosophy, which consequently leads to the state of scientific research in the area of education, 4/ the multiplicity of subjects while studying education (general education, introduction to education, philosophical fundamentals of education, contemporary trends in education, theoretical fundamentals of education, educational doctrines) which blurs the subject and character of education as a science, 5/ the situation of an educatortheorist-researcher (possessing a wealth of knowledge in a specific area; who constructs, organizes and implements the research, very often without any subsidies; writing monographs; winning funds).
Keywords: pedagogika; nauki społeczne